Pengembangan E-Module Berbasis Aplikasi Android Mata Kuliah Listrik dan Elektronika - Ahmad Arif; M. Giatman; Mukhlidi Musykir; Hansi Effendi; Wawan Purwanto; Wagino (Journal for Lesson and Learning Studies, 2022)
Many learning activities still need to run optimally due to the need for supporting teaching materials. It has an impact on low student learning motivation. The research objective is to produce a valid and practical Android application-based E-module. This type of research is Research and Development (R&D) with a 4-D (Four D) development model. In this study, there were two validators, namely material and media validators. The methods used to collect data are observation, interviews, and questionnaires. The instrument used to collect data is a questionnaire. The techniques used to analyze the data are descriptive qualitative analysis, quantitative, and gain score test. The research results are the results of the questionnaire analysis from the validator, obtaining an average value of 0.89, categorized as valid. The practicality questionnaire was filled in by lecturers and students who, after being analyzed, obtained an average score of 88%, which was categorized as very practical. The effectiveness test was carried out based on the KKM scores obtained by students; namely, the score above the KKM was 86%, and the gain score was 0.64, so the E-module being developed can be said to be effective. It was concluded that E-modules based on android applications on electricity and electronics are appropriate to use because they can improve student learning outcomes.